Use of Wide-Host-Range Bacteriophages to Reduce Salmonella on Poultry Products - Donoghue, A.M.; Bielke, L.R.; Higgins, S.E.; Donoghue, D.J.; Hargis, B.M.; Tellez, G. (International Journal of Poultry Science, 2007)
Bacteriophages used to treat infections are typically amplified in a pathogenic host. However, this practice introduces the risk of administering any remaining bacteriophage-resistant pathogen during bacteriophage application if separation techniques are less than perfect. In this study, bacteriophage isolates capable of replicating in both Salmonella and Klebsiella oxytoca were identified and applied to poultry carcasses. These Wide-Host-Range bacteriophages (WHR) were amplified using the non-pathogenic bacteria, Klebsiella oxytoca in tryptic soy broth until a titer of 109 PFU/mL was obtained. WHR and Klebsiella oxytoca were not separated prior to treatment of carcasses. Fresh processed chicken carcasses were inoculated with either Salmonella enteritidis (SE) or S. typhimurium (ST), sprayed with 5 mL of WHR and rinsed with sterile water. Samples were enriched, plated on XLD agar and evaluated for Salmonella-typical colonies. In four separate trials, WHR significantly reduced the recovery of SE. No SE was detected in two trials and a greater than 70% reduction was seen in the other two trials. ST was also significantly reduced in the two trials in which it was included (p<0.05). These experiments suggest that WHR could be an inexpensive and safe method for the reduction of Salmonella on broiler carcasses.